2000
DOI: 10.1210/en.141.12.4558
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins Induce Gremlin, a Protein That Limits Their Activity in Osteoblasts

Abstract: Bone morphogenetic proteins (BMP) induce the differentiation of cells of the osteoblastic lineage and enhance the function of the osteoblast. Growth factor activity is regulated by binding proteins, and we previously showed that BMPs induce noggin, a glycoprotein that binds and blocks BMP action. Recently, additional BMP antagonists, such as gremlin, have been described, but there is no information about their expression or function in osteoblasts. We tested for the expression of gremlin and studied its induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 0 publications
3
64
0
2
Order By: Relevance
“…Nevertheless, various explanations have been suggested for the failure of BMP induction in ASCs and bone marrow stromal cells (BMSCs), including up-regulation of BMP antagonists such as noggin and gremlin (Pereira et al, 2000;Diefenderfer et al, 2003;Sutherland et al, 2004;Zuk et al, 2011). On the other hand, the problem may originate from an insufficient activation of downstream signalling related to phosphorylation and nuclear translocation of certain Smads, the intracellular target proteins of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, various explanations have been suggested for the failure of BMP induction in ASCs and bone marrow stromal cells (BMSCs), including up-regulation of BMP antagonists such as noggin and gremlin (Pereira et al, 2000;Diefenderfer et al, 2003;Sutherland et al, 2004;Zuk et al, 2011). On the other hand, the problem may originate from an insufficient activation of downstream signalling related to phosphorylation and nuclear translocation of certain Smads, the intracellular target proteins of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This activity is normally antagonized by gremlin (Khokha et al, 2003). Gremlin was also upregulated upon activation of ␤-catenin; however, we think that this is a secondary effect, because concurrent expansion of the Bmp target genes Msx1 and Msx2 suggests that active Bmp signaling was occurring in ␤-cat ⌬ex3Prx1/+ limbs, and because Bmps can induce gremlin expression (Pereira et al, 2000).…”
Section: Research Articlementioning
confidence: 92%
“…It was recently shown that expression of drm is under the control of BMP signaling in osteoblasts (Pereira et al, 2000) as well as into chick limb buds. In this case, BMP-soaked beads decreased drm expression in a region close to the BMP source, whereas upregulation occurred at a distance (Capdevila et al, 1999;Merino et al, 1999).…”
Section: Bmps Regulate Drm/gremlin Expressionmentioning
confidence: 99%